Russian Federation : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses key findings of the pilot Fiscal Transparency Evaluation for the Russian Federation. Most aspects of Russia's fiscal reporting and budgeting practices are in line with good or advanced practice under the July 2013 draft of the Fiscal Transparency Code. The disclosure and management of fiscal risks has significantly improved in recent years. The evaluation highlights a number of important areas where fiscal transparency practices could be further improved. Addressing these gaps in fiscal transparency practices would enable the government to provide a more complete picture of its fiscal position, prospects, and risks.